Do all aphids benefit from climate warming? An effect of temperature increase on a native species of temperate climatic zone Cinara juniperi. Issue 2 (2nd April 2016) - Durak, R.; Węgrzyn, E.; Leniowski, K.
Abstract : Global warming has the potential to affect many animal species, in particular temperature-dependent insects with their short generation times and high reproductive rates which facilitate adaptations to long-term climatic fluctuations. Aphids are the model species in studying the association of insect biology with large-scale climate fluctuations because they multiply only within a certain range of temperatures and their rate of development directly depends on temperature. Here, we investigate the effect of climate warming on phenology and voltinism of the juniper aphid ( Cinara juniperi De Geer 1773), a native species of a temperate climate zone in Poland. We also experimentally test for the temperature optimum of the study species. Our study demonstrated that environmental conditions significantly affected phenology of juniper aphid. The timing of larval emergence depended on mean temperatures in March, and in warmer years larvae appeared earlier. The emergence of the sexual generation was related to mean temperatures in August, and higher temperatures resulted in later sexual reproduction. Despite the elongation of the entire life cycle, by almost 3 months, we observed only one additional generation in warmer years. A possible explanation for this pattern may be that the increase in temperature recorded in recent years went beyond the temperature optimum of the study species. Our chamber experiment supports this assumption – juniper aphids developed faster and reproduced more effectively at 20 °C than at 25 °C.